APAKAH BANK ISLAM MALAYSIA MENGELOLA PENGHASILAN DENGAN PROFIT EQUALIZATION RESERVE? - Nissa, Izzun Khoirun (AL HUKMU: Journal of Islamic Law and Economics, 2022)
Income management is not an important factor for PER, because the EBTZP variable is not significant. Future studies need to examine how PER affects capital regulation. The findings of this study indicate that Islamic Banks use PER and IRR to stabilize profits. Although there is empirical evidence on PER behavior and IRR allowance by Islamic Bank institutions, evidence from other financial institutions is still scarce. Based on this research, in the case of Malaysia, there are other institutions that offer Islamic financial products and services, namely developing financial institutions such as Agro Bank, SME Bank, National Savings Bank. These results indicate that Bank Malaysia does not equalize income over time using PER, and in this study it is shown that income management is not an important factor in PER.